Profil Pengaruh Suplementasi L-Lysine HCl dalam Pakan terhadap Dimensi Tubuh Ayam Broiler - Regina Funan; Charles V. Lisnahan; Agustinus Agung Dethan (JAS, 2020)
The purpose of this experiment was to know the effect of L-lysine HCl supplementation in feed on the body dimensions of broilers. This experiment has been carried out in the Housing of Animal Husbandry Study Program, Faculty of Agriculture, the University of Timor for 39 days, from December 2019 to January 2020. The experiment used 80 fourteen-day broilers. The method used in this experiment is a Completely Randomized Design consisting of 4 treatments and 4 replications. The treatments given were T0 (control feed), T1 (L-lysine HCl supplementation 0,35%), T2 (L-lysine HCl supplementation 0,70%), and T3 (L-lysine HCl supplementation 1,00%). The variables observed in this experiment were body length, chest circle, shoulder height, sternum length, femur length, and tibia length. The data obtained were analyzed using Analysis of Variance Analysis and Duncan’s Test. The results of the analysis of variance showed that the treatment had a significant effect on body length, chest circle, shoulder height, sternum length, femur length, and tibia length of broilers (P<0,05). It was concluded that supplementation of 0,70% L-lysine HClin feeds increased the body dimensions of broilers.